Factors of Public Sector Organizational Behaviors that Affect the Personnel Performance Under Sustainable Dynamics of the 21st Century in Nakhon Pathom Provincial Administrative Organization - Jaksudechovanith, Naruedolrapassorn; Wisojsongkram, Siksanee; Jedaman, Pornchai (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
Problems with organizational behavior in the public sector often stem from traditional bureaucratic structures and culture that emphasize rules and centralization of power. This affects the productivity of personnel. This study aims to investigate the factors of public sector organizational behaviors that affect the personnel performance under sustainable dynamics of the 21st century, using the Nakhon Pathom Provincial Administrative Organization as a case study. A mixed-methods sequential design approach, incorporating qualitative studies from document analysis, the interviews among 10 key informants, and a quantitative study using questionnaires with 210 sample groups. The study revealed that public sector organizational factors, including sustainable creative organizational culture, sustainable transformational leadership, sustainable diversity management, and sustainable talent management, have a direct positive influence on sustainable high-performance public sector organizations at the statistically significant level of 0.01. However, a proactive culture, transformational leadership, value-based performance, and a digital mindset are key to effective application.